Proceedings of the Ocean Drilling Program 1998
DOI: 10.2973/odp.proc.sr.160.031.1998
|View full text |Cite
|
Sign up to set email alerts
|

Eratosthenes Seamount: the possible spearhead of incipient continental collision in the Eastern Mediterranean

Abstract: We compare earlier works, based on available geophysical data and plate kinematic considerations, about the origin and evolution of the Eratosthenes structure within the Eastern Mediterranean tectonic framework, with data from Ocean Drilling Program (ODP) Leg 160. The model under discussion is supported by the ODP data regarding the late evolution of the Eratosthenes Seamount; however, deeper drilling is needed for better understanding of the early history of this structure.Analysis of the available seismic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 22 publications
0
37
0
1
Order By: Relevance
“…most recently Tapponnier et al 2004). However, it has long been clear that the Eratosthenes seamount is a continental structure most likely torn from the AfroArabian margin as the eastern Mediterranean was opening (see Kempler 1998;Rybakov and Segev 2004 and the references therein). Here the Troodos was thrust for a very considerable distance and underwent an anticlockwise rotation for some 20° between the Turonian and the Campanian around a pole somewhere east of the present day Hatay, because it has recently turned out that the Hatay ophiolites have rotated in unison with the Troodos nappe (Morris et al 2006; Fig.…”
Section: The Damascene Arcmentioning
confidence: 99%
“…most recently Tapponnier et al 2004). However, it has long been clear that the Eratosthenes seamount is a continental structure most likely torn from the AfroArabian margin as the eastern Mediterranean was opening (see Kempler 1998;Rybakov and Segev 2004 and the references therein). Here the Troodos was thrust for a very considerable distance and underwent an anticlockwise rotation for some 20° between the Turonian and the Campanian around a pole somewhere east of the present day Hatay, because it has recently turned out that the Hatay ophiolites have rotated in unison with the Troodos nappe (Morris et al 2006; Fig.…”
Section: The Damascene Arcmentioning
confidence: 99%
“…The progressive subduction of the Sinai plate beneath the Cyprus Arc was significantly disrupted during the late Pliocene-early Pleistocene with the initiation of the Eratosthenes Seamount-Cyprus Arc collision (Kempler, 1998). On the verge of subduction, tectonic subsidence of Eratosthenes accelerated and the Seamount reached its current vertical position (Robertson, 1998).…”
Section: Cyprus and Eratosthenes Seamountmentioning
confidence: 96%
“…Convergence across the central Cyprus Arc shifted from subduction to collision (Salamon et al, 2003;Hall et al, 2010) while its eastern part exhibits strike-slip motion (Ben-Avraham et al, 1995). Uplift of the island of Cyprus which persisted since the late Miocene accelerated during the early Pleistocene when the island completely emerged from the sea (Kempler, 1998;Harrison et al, 2004). The Troodos Massif and the Kyrenia Range were uplifted in accelerated rates (Robertson and Woodcock, 1986;Robertson et al, 1995;Robertson, 1991, 1998) while NW to NE trending strike-slip faulting became dominant in northern Cyprus (Harrison et al, 2004).…”
Section: Cyprus and Eratosthenes Seamountmentioning
confidence: 99%
“…It has been suggested that there was a terrestrial connection between Anatolia and Cyprus during late Miocene, especially during the desiccation of the Mediterranean in the Messinian. Both lands were again isolated from each other by the beginning of the Pliocene (roughly around 5 My before present) due to reflooding of the Mediterranean (see Kempler, 1998;Robertson, 1998;Hadjisterkotis et al, 2000 for details). Thus, it is more logical to assume that I. mavromoustakisi evolved in a vicariant event from an ancestral stock that remained in Cyprus.…”
Section: Biogeographymentioning
confidence: 99%
“…n. which are described here. The group has an interesting distribution pattern, occurring in Central/Mediterranean Anatolia and Cyprus, two areas that were isolated from each other by the reflooding of the Mediterranean in early Pliocene (Kempler, 1998;Robertson, 1998). Further, these species seem to prefer different altitudes.…”
Section: Introductionmentioning
confidence: 99%